2010
DOI: 10.1007/s10029-010-0699-3
|View full text |Cite
|
Sign up to set email alerts
|

Bochdalek hernia in the adult: demographics, presentation, and surgical management

Abstract: Using modern surgical techniques to include laparoscopy, repair can be performed safely, with a short hospital stay, and with minimal morbidity or mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
151
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(166 citation statements)
references
References 62 publications
8
151
0
7
Order By: Relevance
“…The concept in favor of such an approach is that a significant number of these patients present acutely with serious complications such as strangulation of the gut leading to severe morbidity and mortality. 2,3 This is why we proposed a surgical correction to our patient. In fact, besides having suffered from recurrent respiratory tract infections during childhood, he was diagnosed because of his dorsal pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept in favor of such an approach is that a significant number of these patients present acutely with serious complications such as strangulation of the gut leading to severe morbidity and mortality. 2,3 This is why we proposed a surgical correction to our patient. In fact, besides having suffered from recurrent respiratory tract infections during childhood, he was diagnosed because of his dorsal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Only few reports describe adult patients diagnosed with BH. Brown et al 2 and Machado 3 have extensively reviewed all these reports with the purpose of providing clinicians with an outline for the presentation, work-up and surgical management for adult patients with BH. The incidence is reported to be 0,17% with the majority of hernias occurring on the left side and in male patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. demonstrated that 68% are right sided, but there are under diagnosed because the close of the defect by the liver make them asymptomatic 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiplanar CT and MRI images are useful for showing the diaphragmatic defect (Fig. 15) and the contents of the hernia sac (67,71). This defect is the key finding for differentiating a Bochdalek hernia from diaphragmatic eventration or a diaphragmatic lipoma or liposarcoma (68).…”
Section: Bochdalek Herniamentioning
confidence: 99%